(untitled) (Journal of Universal Science Research, 2023)
Translation of advertising today is singled out as a completely separate area of translator’s activity, which requires from a specialist not only an ideal knowledge of the stylistic subtleties and cultural nuances of Karakalpak and English languages, but also a clear understanding of the consumers’ psychology.